A phenomenological exploration of relationship effort in emerging adult cyclical dating relationships - Knapp, Darin J. (Kansas State University, 2016)
Cyclical romantic relationships—those characterized by breaking up and getting back together or having on/off periods—are a frequent phenomenon in the emerging adult population. These dating relationships maintain some distinctions from other more stable relationships, including the ways that partners strive to sustain relationship health. The purpose of this phenomenological qualitative inquiry was to increase in-depth understanding of how emerging adult dating partners’ relationship effort affects relationship transitions within cyclical dating relationships. Ten heterosexual emerging adult couples (10 men, 10 women) currently in cyclical dating relationships were interviewed about their experiences with relationship effort and maintenance. Participant interviews were analyzed according to the Interpretative Phenomenological Analysis (IPA) method. Specific themes emerged from the data, focusing on how perceived individual effort in the relationship, perceived partner effort in the relationship, and specific maintenance behaviors couples used to sustain relational health affected couple decisions about relationship transitioning. Implications regarding relationship education and clinical intervention among cyclical emerging adult couples are discussed. Future research could focus on continued expansion of understanding when in relationship history cyclical patterns begin, and how partners navigate transitions when both perceive reduced relationship effort.
Keywords: Cyclical relationships; Relationship effort; Relationship maintenance; Emerging adulthood; Relationship churning